PENGARUH GREEN BRAND POSITIONING TERHADAP NIAT PEMBELIAN DIMEDIASI OLEH SIKAP (KASUS THE BODY SHOP BALI) - Wati, Dewa Ayu Sri Pradnya; Ekawati, Ni Wayan (E-Jurnal Manajemen, 2016)
ABSTRACT The study aims to determine the effect of green brand positioning on purchase intentions that mediated by attitude on products the body shop. The object of this study is products The Body Shop. This study was counducted in Denpasar. The sampling method used in this research is non-probability sampling method with purposive sampling technique. Data were collected using questionnaire with Likert scale, and a sample of 100 respondents has been collected. The data was analysed using path analysis.The findings of this study revealed that: (1) green brand positioning has a positive and significant effect on attitude consumer the body shop; (2) attitude consumer has a positive and significant effect on purchase intentions the body shop products in Denpasar city; (3) green brand positioning has a positive and significant effect on purchase intentions the body shop products; (4) attitude contribute significant mediated the relation between of green brand positioning on purchase intentions the body shop products in Denpasar city.
Keywords: attitude, positioning, purchase intentions